Influence of Lithium Diffusion into Copper Current Collectors on Lithium Electrodeposition in Anode‐Free Lithium‐Metal Batteries - Huang, Yu‐Kai; Chen, Heyin; Nyholm, Leif (Small (Weinheim an der Bergstrasse, Germany), 2023)
The development of “anode‐free” lithium‐metal batteries with high energy densities is, at present, mainly limited by the poor control of the nucleation of lithium directly on the copper current collector, especially in conventional carbonate electrolytes. It is therefore essential to improve the understanding of the lithium nucleation process and its interactions with the copper substrate. In this study, it is shown that diffusion of lithium into the copper substrate, most likely via the grain boundaries, can significantly influence the nucleation process. Such diffusion makes it more difficult to obtain a great number of homogeneously distributed lithium nuclei on the copper surface and thus leads to inhomogeneous electrodeposition. It is, however, demonstrated that the nucleation of lithium on copper is significantly improved if an initial chemical prelithiation of the copper surface is performed. This prelithiation saturates the copper surface with lithium and hence decreases the influence of lithium diffusion via the grain boundaries. In this way, the lithium nucleation can be made to take place more homogenously, especially when a short potentiostatic nucleation pulse that can generate a large number of nuclei on the surface of the copper substrate is applied. Diffusion of lithium into the copper substrate, most likely via the grain boundaries, can significantly influence the nucleation process by making it more difficult to obtain a great number of homogeneously‐distributed lithium nuclei on the copper surface and thus leads to inhomogeneous electrodeposition. This problem can be mitigated by an initial chemical prelithiation of the copper surface.